Microstructure and microhardness of melt-spun Al–25Si–5Fe–XCo (X=0, 1, 3, 5) alloys - Kilicaslan, M. Fatih; Yilmaz, Fikret; Ergen, Semra; Hong, Soon-Jik; Uzun, Orhan (Elsevier BV, 2013)
Abstract The microstructure and microhardness evolution of melt-spun Al–25Si–5Fe alloy with Co addition (1, 3 and 5 wt.%) were investigated. Microstructural and spectroscopic analyses demonstrate that Co could refine primary Si grains and change their morphology because it causes higher constitutional undercooling and has large mixing enthalpy with Si. Especially, 3 wt.% Co addition causes homogeneously distributed fine spherical Si particles in the rapidly solidified Al–25Si–5Fe alloy. The size of the spherical silicon particles was from around 200 to 600 nm near the wheel side region, and it varied from 800 nm to 1.3 μm at the air side. The optimum ratio of Si and Co should be between 6 and 8.3 to form spherical Si grains in Al–25/30Si–5Fe alloys. A considerable improvement in microhardness value (from 211 to 370 HV) was obtained with the addition of Co.
Keywords: nano-technology; mechanical engineering; engineering and technology